2014
DOI: 10.1007/978-3-319-10503-1_2
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Sexual Cycle in Filamentous Ascomycetes

Abstract: The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specifi c statement, that such names are exempt from the relevant protective laws and regulations and therefore free for general use. While the advice and information in this book are believed to be true and accurate at the date of publication, neither the authors nor the editors nor the publisher can accept any legal responsibility for any errors or omissions tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…Although some indirect evidence for the occurrence of sexual reproduction was observed in some Penicillium species (Ropars et al., ), only a minority of species produced these typical sexual structures (Bohm et al., ; Ropars et al., ; Visagie et al., ). For most fungi, it is more difficult to produce a sexual state under laboratory conditions than in nature, because the artificial incubation conditions can block their interaction with other mating types (Houbraken and Dyer, ). It is also not uncommon for strains to lose the ability to reproduce sexually like P. brefeldianum (CBS 235.81), which has been observed to produce a sexual stage but not under laboratory conditions (Visagie et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Although some indirect evidence for the occurrence of sexual reproduction was observed in some Penicillium species (Ropars et al., ), only a minority of species produced these typical sexual structures (Bohm et al., ; Ropars et al., ; Visagie et al., ). For most fungi, it is more difficult to produce a sexual state under laboratory conditions than in nature, because the artificial incubation conditions can block their interaction with other mating types (Houbraken and Dyer, ). It is also not uncommon for strains to lose the ability to reproduce sexually like P. brefeldianum (CBS 235.81), which has been observed to produce a sexual stage but not under laboratory conditions (Visagie et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Microscopic observations of compatible isolates on WA indicated that the hyphae of individuals of opposite mating-types interwove and produced a coherent hyphal matrix; thus, a lack of physical association of opposite mating-types was discounted as a reason for the absence of pseudothecia. Furthermore, conditions of incubation covered a range of conditions used to produce pseudothecia in closely related species (Chilvers et al 2009;Houbraken and Dyer 2014). Thus, the sexual morph is proposed to be induced under highly specific environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the identification of the genes, the availability of genome sequences allows the design of mating-type specific primers, which can be used to rapidly distinguish opposite mating-type strains. Therefore, targeted crossings between opposite mating-type strains can be easily set-up [32]. Next to the detection of sex-related genes, the advances in transcriptomics and the increasing availability of RNA-Seq data also allows the investigation of whether these genes are transcribed and to get an insight into their functionality.…”
Section: Advances In the Genomic Technologies Show Evidence Of Sexualmentioning
confidence: 99%